Higher oxidative balance score decreases risk of stroke in US adults: evidence from a cross-sectional study - Zhan, Fangfang; Lin, Gaoteng; Duan, Kefei; Huang, Bixia; Chen, Longfei; Ni, Jun (Frontiers in Cardiovascular Medicine, 2023)
The oxidative balance score (OBS) can be used to represent the overall burden of oxidative stress in an individual. This study aimed to explore the association between the risk of stroke and OBS.The National Health and Nutrition Examination Survey (NHANES) from 1999 to 2018 was used to extract a series of variables for participants who took the stroke questionnaire. The construction of OBS relied on diet and lifestyle components, which included sixteen nutrients and four lifestyle factors.Weighted multivariable-adjusted logistic regression was performed to investigate the association between the stroke risk and OBS. A stratified analysis was also conducted.The dose-response relationship between stroke risk and OBS was elucidated by performing a restricted cubic spline function.Results: A total of 20680 participants were included for analysis, 768 of whom suffered from stroke. Based on weighted multivariable logistic regression analysis, we discovered that the stroke prevalence decreased by 2% for each OBS unit added (OR: 0.98 (0.97-1.00), P<0.01). For the OBS subgroup, we also discovered that higher OBS was related to a reduction in the risk of stroke (Q4 vs Q1: OR:0.65 (0.46-0.90), P<0.01). The prevalence of stroke declined by 3% with every OBS unit added to the diet component (OR: 0.97 (0.96-0.99), P < 0.01). For the dietary OBS subgroup, higher OBS in diet component was associated with a decrease in the prevalence of stroke (Q4 vs Q1: OR: 0.65, (0.47-0.91), P <0.05). Further stratified analysis showed that every OBS unit raised associated with a declined risk of stroke prevalence was statistically significant in participants in subgroups of >=60 years, female, no-diabetes mellitus and no-hypertension. OBS and stroke prevalence was correlated in a linear manner.The study found that a higher OBS was associated with a decrease in stroke prevalence, which could be a significant indicator for evaluating stroke risk.